The Nan Local Wisdom : The Unseen Manuscripts - Kotsupho, Phisit (Journal of International Buddhist Studies, 2016)
The Text entitled The Nan Local Wisdom : The Unseen Menu Scripts is selected local knowledge which recorded in Palm Leaves and Traditional handmade Sar Paper those found at three Temples of Nan Province; i.e. Wat Don Keaw, Muang District, Wat Na Luang Nai and Wat Sri Chiang Barn, Wiang Sa District. Theses texts were especially regarded as the wise Compositional Works of Nan Scholars. They have neither been transliterated nor published. With this reason supporting, they have to be truly named “the Nan Unseen Issues”. They are as follows ;1) Anisong Kor Phrathat(Don Kaew) ; The good result on Building Jetiya written by Ven. Suriya, the Departed Abbot of Wat Don Kaew. It recorded in detail about how to construct Jetiya since the time he got the Buddha Relics until setting the plan and style of Jetiya, selection of the skillful Builders, the materials, the construction and it’s jubilation.2) The Tam Nan Tham Kum (Guhaghataka); the Legend of Kum Caves was rewritten by Saen Thananjaya. It was the record of the invasion of Buddhism to Lan Na Yonok Chiang Saen by the Buddha. It told that when the Buddha with his attendant, Ananda came to Dhaja Pabbata; the peak of Flag in the North area near the border of Myamar, and sit on the Rock. The Buddha forecasted the stories those will be occurred in the future that; the right here sitting place shall be the Buddha’s Relic Located thereby it shall prolong 5,000 years of Buddhism. After the passing away of the Buddha, Ven.Phramaha Kassapa, the Great Elder, broght Buddha’s Relics to that Peak of Mountain. At that time, the Ruller named Ajuttaraj, the Loajok’s Grandson, having known the purpose of the Elder, then, got togather with his people embedded the Buddha’s Relic on the stone plate and built Jetiya on the top. He assigned the Lua Leader to take care that Sacred Area, and left 500 families to guard and support the Jetiya. Surrounding that hill peak, there were 12 Holy Wells, a lot of caves, such as Kum Cave whereby kept 4 pots, the Fish Cave and Plew Plong Fa Cave, etc. People, since those days, worshiped Buddha Relic and handed down the tradition of Buddha Relic worship upto now. 3) The Nan book of Elephant Characteristics and Elephant blessing ceremony Verses. This book was the personal Treasure of Her Highness Thip, the Last Nan Ruller His Highness Mahaphomsurathada’s Wife. It informed the good and bad Characters of Elephants. There is the Local ancient knowledge about medical treatment of the ill elephants. Additionally there are 7 versions. 4) The Mangala Dhamma Poem ; Phrajayanandamuni(Wong), the Nan fomer Monk Provincial Governor. It is the teaching poem based on 38 prosperities which used the Nan Local old style language. These 4 books are the prominent works selected from the 2014 research project entitled : The investigation, Collection and Management the Information System of Nan Province Palm Leaf Manuscript’s Copy in Chao Ananta Worariddhidej Period. They are more valuable to transliterate into modern Thai Language and published for the advantage of Society.